The Landscape of High-Risk HPV Genotypes in Cervical Lesions in Bangladesh: A Systematic Literature Review - Begum, Shirin Akter; Mahmud, Tasfia; Amatullah, Mehriban; Afroz, Romena; Amin, Md. Nurul; Nessa, Ashrafun (Journal of Posthumanism, 2025)
Cervical cancer is a leading cause of cancer-related mortality among women worldwide, particularly in low- and middle-income countries such as Bangladesh. Persistent infection with high-risk human papillomavirus (hr-HPV) is the primary etiological factor in cervical carcinogenesis. Understanding the prevalence and distribution of hr-HPV genotypes associated with cervical lesions in Bangladesh is crucial for designing targeted vaccination and screening programs.This review followed PRISMA guidelines. A comprehensive search was conducted in PubMed, Scopus, Web of Science, Google Scholar, and Cochrane Library. Studies were included if they reported HR-HPV prevalence and genotype distribution among women with cervical lesions in Bangladesh. A total of 35 records were screened, 20 full texts were reviewed, and 10 met the inclusion criteria. Data extraction covered study characteristics, HPV genotypes, detection methods, and lesion associations. Quality assessment tools appropriate to the study design were applied.Across the included studies, hr-HPV prevalence ranged from 58% to over 90% among women with cervical lesions. HPV-16 and HPV-18 were consistently the most common genotypes, with additional detection of HPV-52, HPV-58, and HPV-45. Squamous cell carcinoma was more frequently HPV-positive than adenocarcinoma. HPV-negative cervical cancers were rare but reported.This review confirms the predominance of HPV-16 and HPV-18 in cervical lesions in Bangladesh. The findings highlight the urgent need to expand HPV vaccination coverage, strengthen national screening programs, and improve genotype surveillance. By aligning vaccine formulation and screening policy with local epidemiology, Bangladesh can advance towards achieving the WHO’s cervical cancer elimination goals by 2030.